STAFF ACTIVE AND REFLECTIVE LEARNING (ARL) TO ENHANCE STUDENT MANAGEMENT - Leong, Tay Sing; Yew, Lim See (Journal of Technical Education and Training, 2010)
The Staff Active Reflective Learning (ARL) is a new scheme designed to enhance student management though regular get-togethers of a group of teaching staff. It provides a platform for staff to share issues related to teaching, and seek solutions. This addresses current and future challenges faced in classroom management. The implementation of the Staff ARL is one of the recent initiatives taken under a new approach to shared learning within the School of Electronic and Info-Comm Technology. It provides a platform for mentors to facilitate in developing fellow staff members through the provision of professional support, helping existing staff to learn and grow professionally. Insights into classroom management techniques are provided for new staff to apply while waiting to attend the formal Pedagogic Certification in Technical Education (a compulsory component for all staff). The Staff ARL fosters good working relationships, as staff can ‘chill out’ and be rewarded through the enrichment of knowledge, sharpening of capabilities, building of confidence, and growth of mutual support. The scheme received good feedback as it resulted in the creation of a range of purposeful learning tools and strategies for thedevelopment of problem solving skills, reflective thinking skills and awareness of upto-date classroom situations.